ANALISIS GROWTH OPPORTUNITY PADA PT. ADIRA DINAMIKA MULTIFINANCE TBK - Raodah, Raodah; Pratiwi, Aliah (Universitas Muhammadiyah Palembang, 2020)
This study aims to determine the level of Growth Opportunity at PT. Adira Dinamika Multifinance Tbk. Growth Opportunity is a growth opportunity for a company in the future. The research method used in this research is descriptive research. The research instrument used was financial statement data in the form of a balance sheet. the population used is the company's financial statement data for 28 years and the sample used in this study is financial data for 10 years namely (2009-2018). Data collection techniques used were literature study and data analysis techniques used were t one sample. Based on the results of the study it can be concluded that the Growth Opportunity INVOS and IOE in the 10 years of the research period is getting better and tends to increase.